Sacred Cleanlines, Silent Ecology : Ritual Communication and Environmental Awarenenss in Indonesia Pesantren - Mutiara Rahmadini Setya Lestari; Desi Dwi Prianti (Universitas Brawijaya, 2025)
This study examines how Islamic boarding schools (pesantren) function as community-based institutions that actively foster environmental awareness through daily practices and ritual communication. Focusing on the Ketapang Kepanjen Islamic boarding school, this study uses a cultural studies perspective and adopts James Carey's model of communication as ritual to explore how environmental values are embedded, practised, and internalised by santri (students) in the boarding school environment. Contrary to the dominant discourse that often associates Islamic schools with dogmatism, or even extremism, this study highlights pesantren as places of cultural transmission where ecological ethics are lived out as part of religious life. Although pesantren administrators and santri may not explicitly identify their practices as environmental activism, values such as cleanliness, moderation, collective responsibility, and respect for nature are consistently emphasized through daily routines, religious teachings, and comelan rituals. These actions are not framed as direct environmental care, but are rooted in Islamic principles that inherently advocate ecological balance. By documenting and analyzing these practices through participatory observation, this study reveals how ritual communication in pesantren life fosters a culturally embedded form of environmental awareness, rooted in spirituality, contributing to sustainable behavior that is in harmony with the moral and communal ethos of the pesantren.